Carta de Francis Robinson a Emilio S. Belaval - Robinson, Francis; Belaval, Emilio S. (My University, 1975)
Francis Robinson agradece a Emilio S. Belaval por el anuncio en el debut.
Keywords: Robinson, Francis--Correspondence.; Robinson, Francis--Correspondencia.; Belaval Maldonado, Emilio S.--Correspondence.; Belaval Maldonado, Emilio S.--Correspondencia.